2008
DOI: 10.1007/s00508-008-1011-8
|View full text |Cite
|
Sign up to set email alerts
|

Needlestick injuries among health care workers: Occupational hazard or avoidable hazard?

Abstract: Occupational exposure to blood is a common problem among healthcare workers. The introduction of safety devises is one of the main starting points for avoidance of needlestick injuries, and acceptance among healthcare workers is high. Further targets for preventive measures, such as training in safe working routines, are necessary for improvement of safe work conditions.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

6
25
2
8

Year Published

2008
2008
2014
2014

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 40 publications
(41 citation statements)
references
References 21 publications
6
25
2
8
Order By: Relevance
“…The studies from Alexandria hospital [16] Egypt (67.9%), a study from Nigeria [17] involving primary health care workers (57.1%) and a study from Pakistan [18] involving health care workers of two tertiary care hospitals comprising both public and private health sector (64%) have shown marginally lower percentage of needle stick injuries in relation to the present study observation. In contrast to the present study findings, studies from Germany [3,19] Maharashtra-India [13] and Mongolia [20,21] have shown significant lower proportion of needle stick injuries i.e. 31.5%, 49.1% and 38.4% respectively among the health care personnel.…”
Section: Discussioncontrasting
confidence: 99%
“…The studies from Alexandria hospital [16] Egypt (67.9%), a study from Nigeria [17] involving primary health care workers (57.1%) and a study from Pakistan [18] involving health care workers of two tertiary care hospitals comprising both public and private health sector (64%) have shown marginally lower percentage of needle stick injuries in relation to the present study observation. In contrast to the present study findings, studies from Germany [3,19] Maharashtra-India [13] and Mongolia [20,21] have shown significant lower proportion of needle stick injuries i.e. 31.5%, 49.1% and 38.4% respectively among the health care personnel.…”
Section: Discussioncontrasting
confidence: 99%
“…The data of Wicker et al studies [27] and a Japanese teaching hospital also showed a poor reporting rate [28]. Nonreporting rates between 45 and 75 % have been published recently [29][30][31][32]. Factors contributing to low reporting rates include: healthcare workers' perception of risk, occupation [30], length of service [31], lack of time, and poor follow-up care [32].…”
Section: Discussionmentioning
confidence: 99%
“…A study of risk factors for the occurrence of percutaneous accidents in the nursing team identified higher chances of accidents among nursing workers who assessed the risk of suffering percutaneous accidents at their workplace as low than among those who assessed it as high [18]. Health professionals' underestimation of the risk of bloodborne pathogen transmission has been reported in different studies as a motive for accident under-reporting [4,14,16,19]. As HIV, HBV and HCV prevalence rates can be very different, depending on the study region, the population attended at each institution and the fact that many patients are hospitalized due to other causes, not related to the infections these viruses cause, it is dangerous for professionals themselves to judge accident severity, which should be the responsibility of specialized and experienced professionals.…”
Section: Discussionmentioning
confidence: 99%
“…Under-reporting rates can vary according to the professional category [4] and exposure type [5], with higher rates in case of nonintact skin (87%) and mucous tissue (77%) exposure to blood and 51% in case of percutaneous injuries. In addition, the way these data were collected could also interfere with the rates [6].…”
Section: Introductionmentioning
confidence: 99%